Analysis of The Relationship between Blood Groups and Lung Cancer Risk_x000D_ Depending on Histology - (:unkn) unknown (My University, 2021)
Aim: Blood group antigens are the first genetic markers discovered. ABO blood groups which are expressed on redblood cell membranes are reported to be associated with malignancy risk. The present study aimed to investigatewhether there is an association between blood groups and patients with lung cancer.Material and Methods: In our study, ıt was reviewed 587 patients with lung cancer whose ABO/Rh blood types wereserologically confirmed. Patients were classified according to blood groups (O, A, B, AB), Rh factor (+, −) andhistological types of lung cancer as Non-small cell lung carcinoma (NSCLC) and Small cell lung carcinoma (SCLC).The adenocarcinoma (AC) and squamous carcinoma (SC) as subtypes of NSCLC were recorded. The relationship ofABO/Rh blood groups with clinical features, such as age, sex and histological subtype were evaluated.Results: There was no significant association between pathological results and blood groups O, A, B and AB. SCLCpatients had significantly higher frequency of blood type B Rh (-) when compared to NSCLC patients.Conclusion: We observed an association between risk of lung cancer and ABO blood groups. Although the Rh factor isnot effective by itself, patients with the B Rh (-) blood group may have a higher risk than SCLC. Examining therelationship of blood group subtypes with lung cancer cells at the molecular level would be useful to clarify therelationship between lung cancer and blood groups.

Amaç: Kan grubu antijenleri, keşfedilen ilk genetik belirteçlerdir. Kırmızı kan hücre zarlarından eksprese edilen ABO_x000D_ kan gruplarının çeşitli çalışmalarda malignite riski ile ilişkili olduğu gösterilmiştir. Bu çalışmanın amacı, kan grupları_x000D_ ile akciğer kanseri arasında bir ilişki olup olmadığını araştırmaktır._x000D_ Gereç Yöntemler: Çalışmamızda ABO ve Rh kan grubu serolojik olarak doğrulanmış 587 akciğer kanserli hasta_x000D_ gözden geçirildi. Hastalar kan gruplarına (O, A, B, AB), Rh faktörü (+, -) ve histolojik akciğer kanseri tiplerine göre_x000D_ [Küçük Hücreli Dışı Akciğer kanseri (KHDAK) ve Küçük Hücreli Akciğer Kanseri (KHAK)] sınıflandırıldı._x000D_ KHDAK’nin adenokarsinom (AK) ve skuamöz karsinom (SK) alt tipleri kaydedildi. ABO / Rh kan gruplarının yaş,_x000D_ cinsiyet ve histolojik alt tip gibi klinik özelliklerle ilişkisi değerlendirildi._x000D_ Bulgular: Patolojik analiz sonucu ile O, A, B ve AB kan grupları arasında anlamlı bir ilişki bulunmadı. Çalışmada_x000D_ KHAK'li olgularda B Rh (-) kan grubuna sahip olan hastaların oranı, KHDAK'li olanlardan daha yüksek bulundu._x000D_ Sonuç: Akciğer kanseri riski ile ABO kan grupları arasında bir ilişki olduğu görüldü. Rh faktörü tek başına etkili_x000D_ olmamakla beraber B Rh (-) kan grubuna sahip olan hastalar KHAK açısından daha fazla riske sahip olabilir. Kan grubu_x000D_ alt tiplerinin akciğer kanseri hücreleriyle moleküler düzeyde ilişkisinin incelenmesi, akciğer kanseri ve kan grupları_x000D_ arasındaki ilişkiyi açıklığa kavuşturmak için yararlı olacaktır.
Kan Grupları ile Akciğer Kanseri Riski Arasındaki İlişkilerin Histolojiye Bağlı Analizi